Pectus excavatum - Robbins, Langan P. (Radiol Case Rep, 2015)
In pectus excavatum, a developmental chest-wall deformity that affects approximately one in 400 births, the sternum is depressed inward and the ribs protrude anteriorly. This deformity can compromise pulmonary and/or cardiac function. It can also produce a characteristic radiographic appearance on frontal radiographs, which may be mistaken for right-middle-lobe opacification from pneumonia or atelectasis. I present a case of pectus excavatum in a teenage female with characteristic imaging findings, and the disposition of the case.